A high-efficiency trichome collection system by laser capture microdissection - Qin, Wei; Li, Yongpeng; Peng, Bowen; Liu, Hang; Chen, Tiantian; Yan, Xin; Zhang, Yaojie; Wang, Chen; Yao, Xinghao; Fu, Xueqing; Li, Ling; Tang, Kexuan (Frontiers in Plant Science, 2022)
Trichomes, which are classified as glandular or non-glandular, are hair-like epidermal structures that are present on aerial parts of most plant species. Glandular secretory trichomes (GSTs) have the capacity to secrete and store specialized metabolites, which are widely used as natural pesticides, food additives, fragrance ingredients or pharmaceuticals. Isolating individual trichomes is an essential way for identifying trichome-specific gene functions and discovering novel metabolites. However, the isolation of trichomes is difficult and time-consuming. Here we report a method to isolate the GSTs from leaf epidermis dispense with fixation using laser capture microdissection (LCM). In this study, 150 GSTs were captured efficiently from Artemisia annua leaves and enriched for artemisinin measurement. UPLC analysis of microdissected samples indicated specific accumulation of secondary metabolites could be detected from a small number of GSTs. In addition, qRT-PCR revealed that the GST-specific structural genes involved in artemisinin biosynthesis pathway were highly expressed in GSTs. Taken together, we developed an efficient method to collect comparatively pure GSTs from unfixed leaved, so that the metabolites were relatively obtained intact. This method can be implemented in metabolomics research of purely specific plant cell populations and has the potential to discover novel secondary metabolites.